System of activities by using active methods for improving the english language writing skills - Benítez Duchitanga, Adriana Anahí; Gaona León, Joselyn Micaela (Benítez Duchitanga A. A., Gaona Leon J. M., (2022) system of activities by using active methods for improving the english language writing skills. (Trabajo de Titulación). UTMACH, Facultad De ciencias Sociales, Machala, Ecuador. 83 p., 2022)
The following research work aims to improve the English language writing skills of the second-level students of CEC in the period June-July 2021 by using active methods, because, even though the Ministry of Education has modified certain aspects of the teaching/learning process of the English language in the country, there are still difficulties that limit students in the classroom to develop their communicative competences, particularly in the ability to write. The research has as object of study the teaching-learning process of the English language as a foreign language in the second level of the CEC, besides It is based on a qualitative paradigm of non-experimental and propositional, making use of theoretical methods that facilitated the analysis and explanation of the object of study, as well as the support of empirical methods for data collection, such as interviews with students and participant observation. In this way, in response to the needs of the population, a system of didactic activities is provided using active methods, favoring the development of critical thinking and student creativity.
El siguiente trabajo investigativo tiene como finalidad el mejoramiento de la habilidad de expresión escrita en inglés en los estudiantes universitarios de segundo nivel del CEC (MACHALA) durante el periodo Junio-Julio 2021 empleando métodos activos, debido a que, aunque el ministerio de educación ha modificado ciertos aspectos del proceso de enseñanza/aprendizaje del idioma en inglés en el país, aún existen dificultades que limitan a los estudiantes dentro del aula de clase a desarrollar sus competencias comunicativas particularmente en la habilidad de escritura. La investigación tiene como objeto de estudio el proceso de enseñanza- aprendizaje del idioma inglés como lengua extranjera en el segundo nivel del CEC, además se encuentra sustentada bajo un paradigma cualitativo de carácter no experimental y de tipo propositiva, haciendo uso de métodos teóricos que facilitaron el análisis y la explicación del objeto de estudio, de igual forma el apoyo de los métodos empíricos para la recolección de datos tales como; la entrevista a los estudiantes y la observación participante. De este modo en respuesta a las necesidades de la población se aporta con un sistema de actividades didácticas empleando métodos activos, favoreciendo al desarrollo del pensamiento crítico y la creatividad del estudiante.
Keywords: SYSTEM OF DIDACTIC ACTIVITY; ACTIVE METHOD; TEACHING-LEARNING PROCESS